Boron Isotopic Analysis of Representative Atmospheric Aerosols Derived From Long-Range Transported/Local Emission on an Islet Offshore NE Taiwan - Lin, Yen-Po; You, Chen-Feng; Kao, Tsung-Yu; Chung, Chuan-Hsiung; Hung, Chung-Chieh Gary (Frontiers in Environmental Science, 2021)
To identify pollutant origins and their potential sources from either long-range transported (LRT) or local emissions, the concentrations and isotopic compositions of Boron (B) were measured in the water-soluble fraction of aerosol specimens. The samples were collected on Peng Chia Yu (PCY), a non-residential islet offshore in northeastern Taiwan for 26 months from January 1998 to March 2000. This islet potentially inhibits various sources of pollutants or natural chemical transportation during monsoon periods and suffers minimal human perturbation. The B concentrations in aerosols are 0.3–1.63 ng m-3 during the SW monsoon when compared with 0.46–2.56 ng m-3 during the NE monsoon. However, boron isotopic compositions (δ11B) showed no clear seasonal variations in the same specimens during both monsoons (δ11B = 10.7–24.3‰), regardless of any differences in air mass origin. Two potential end-member mixing scenarios are proposed by applying a simple mixing model using δ11B and the B/Na ratio. One end member is ocean sea-salt that is characterized by low B/Na and high δ11B and the other is the anthropogenic contributions that are characterized by high B/Na and low δ11B (δ11B < 10‰). Based on these results, the aerosol emissions in Northern Taiwan showed low B concentrations, near constant δ11B values when compared with long-range transported ones from other nearby regions. This study provides preliminary B and δ11B levels in aerosols that are derived from LRT/local emissions and monsoonal effects on aerosols collected offshore at PCY in NE Taiwan.